2003
DOI: 10.1053/rmed.2003.1448
|View full text |Cite
|
Sign up to set email alerts
|

Perception of dyspnea during exercise-induced bronchoconstriction

Abstract: We conclude that dyspnea recorded in the laboratory after exercise test is related to exertional symptoms reported during real life, but not completely related to EIB. The rating of dyspnea is a well-suited model to study naturally occurring exercise-induced dyspnea and a useful tool to enlarge the results of an exercise challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…This may be a relevant limitation of our study. The poor correlation between self-reported ERRS and the results of specific exercise tests has been shown previously and there is a rather high frequency of false positive and false negative results [8, 11-13, 29, 30]. In the study by Panditi et al, the severity of ERRS during the precedent week was not related to any of the parameters of the EIB test and the parent’s perception of ERRS in their children was very poorly related to the symptom perception by the children [12].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This may be a relevant limitation of our study. The poor correlation between self-reported ERRS and the results of specific exercise tests has been shown previously and there is a rather high frequency of false positive and false negative results [8, 11-13, 29, 30]. In the study by Panditi et al, the severity of ERRS during the precedent week was not related to any of the parameters of the EIB test and the parent’s perception of ERRS in their children was very poorly related to the symptom perception by the children [12].…”
Section: Discussionmentioning
confidence: 93%
“…The available data on the relationship between reported exercise-related respiratory symptoms (ERRS) such as breathlessness or dyspnea and the magnitude of bronchoconstriction after an exercise test in the laboratory are very controversial. Some authors have shown that ERRS are predictive for exercise-induced bronchoconstriction (EIB) [8, 9], whereas others found no or a poor relationship between the reported ERRS and the results of specific exercise testing [10-14]. Several recent studies have shown a poor predictive value for the asthma control test (ACT) or the asthma control questionnaire (ACQ) in predicting EIB in asthmatic children with a high percentage of children showing a positive EIB test despite reporting well-controlled asthma according to the ACT or ACQ [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the DPI device, elderly patients and/or those with more severe COPD may be unable to achieve a suffi cient peak inspiratory fl ow rate for optimal drug delivery ( Figure 1B-C). 11,13,28,31,[44][45][46] Different DPI models operate dissimilarly from one another in loading and priming of the device. Therefore, DPI devices cannot be interchanged with the assumption that they will work in the same way, and deliver an equivalent dose to the patient's lungs.…”
Section: Dry Powder Inhalersmentioning
confidence: 99%
“…EIB may be associated with cough, wheeze, chest pain or tightness, dyspnoea or excessive mucus production 6. However, the amount of bronchoconstriction does not always correlate well with the baseline level of lung function or presence or severity of symptoms 7 8. Nevertheless, these symptoms or the effect of bronchoconstriction on ventilation could limit athletic performance.…”
Section: Introductionmentioning
confidence: 99%